Linking Constitutional and Environmental Rights: Applying section 7 of the Canadian Charter of Rights and Freedoms to adverse environmental impacts - DeWolf, Julie (University of Waterloo, 2015)
Many Canadians are currently exposed to adverse environmental impacts on a regular basis, often from activities that have received government authorization. There has been a recent push from mainstream and political actors to incorporate environmental rights into the Canadian legal system to address this issue. Two proposed methods include the enactment of an Environmental Bill of Rights and an amendment to the Canadian Charter of Rights and Freedoms (the Charter) to constitutionalize an explicit right to a healthy environment. However, there are limitations to both of these approaches. A statutory Bill of Rights does not have the teeth of constitutional rights, and an amendment to the Constitution is, due to the strict amendment requirements provided in subsection 38(1) of the Constitution Act, 1982, at best a long-term goal. Section 7 of the Charter – the right to life, liberty, and security of the person and the right not to be deprived thereof except in accordance with the principles of fundamental justice – is another option. The case law on section 7 indicates that serious health risks can cause physical deprivations of security of the person. However, there is legal uncertainty in relation to how specific environmental harms may intersect with the security of the person and how these deprivations would violate the principles of fundamental justice. This thesis concludes that section 7 can apply when the substance of a claim relates to the environment. Specifically, the case law demonstrates that the best argument available for section 7 is that procedural fairness, as a principle of fundamental justice, requires governments to provide specific procedural protections when regulatory approvals pose substantial health risks that interfere with affected individuals’ rights to security of the person. Such approval processes must meet the minimum requirements of procedural fairness when section 7 rights are at stake: notice, participation, and the provision of reasons. Further, the rule of law and the rule against arbitrariness require that final decisions about those projects be made rationally. Decisions must reflect the purpose of the legislation that grants power to the decision-makers, and take into account any factually sound evidence – including scientific evidence – that is presented.
Keywords: environmental rights; Canadian Charter of Rights and Freedoms; security of the person; procedural fairness; Environmental and Resource Studies